Targeted Propolis-Loaded Poly (Butyl) Cyanoacrylate Nanoparticles: An Alternative Drug Delivery Tool for the Treatment of Cryptococcal Meningitis - Patcharin Thammasit; Patcharin Thammasit; Patcharin Thammasit; Chayada Sitthidet Tharinjaroen; Chayada Sitthidet Tharinjaroen; Yingmanee Tragoolpua; Volker Rickerts; Radostina Georgieva; Radostina Georgieva; Hans Bäumler; Khajornsak Tragoolpua; Khajornsak Tragoolpua (Frontiers Media S.A., 2021)
In this study, we describe a nano-carrier system for propolis that is able to cross an in vitro model of the blood-brain barrier (BBB) and effectively reduce the virulence of Cryptococcus neoformans in animal models. Antimicrobial properties of propolis have been widely studied. However, propolis applications are limited by its low water solubility and poor bioavailability. Therefore, we recently formulated novel poly (n-butyl cyanoacrylate) nanoparticles (PBCA-NP) containing propolis. PBCA-NP are biocompatible, biodegradable and have been shown to effectively cross the BBB using apolipoprotein E (ApoE) as a ligand. Prepared nanoparticles were characterized for particle size, zeta potential, propolis entrapment efficiency and in vitro release. Additionally, the PBCA-NP were functionalized with polysorbate 80, which then specifically adsorbs ApoE. Using an in vitro BBB model of human brain microvascular endothelial cells hCMEC/D3, it was shown that fluorescence labelled ApoE-functionalized PBCA-NP were internalized by the cells and translocated across the cell monolayer. Propolis-loaded PBCA-NP had in vitro, antifungal activity against C. neoformans, which causes meningitis. To utilize the invertebrate model, Galleria mellonella larvae were infected with C. neoformans and treated with propolis-loaded PBCA-NP. The larvae exhibited normal behavior in toxicity testing, and treatment with propolis-loaded PBCA-NP increased survival in the C. neoformans-infected larvae group. In addition, following cryptococcal infection and then 7 days of treatment, the tissue fungal burden of mice treated with propolis-loaded PBCA-NP was significantly lower than control groups. Therefore, our ApoE-functionalized propolis-loaded PBCA-NP can be deemed as a potential targeted nanoparticle in the therapeutic treatment of cerebral cryptococcosis.